Differential responses to high- and low-dose ultraviolet-B stress in tobacco Bright Yellow-2 cells - Takahashi, Shinya; Kojo, Kei H.; Kutsuna, Natsumaro; Endo, Masaki; Toki, Seiichi; Isoda, Hiroko; Hasezawa, Seiichiro (Frontiers in Plant Science, 2015)
Ultraviolet (UV)-B irradiation leads to DNA damage, cell cycle arrest, growth inhibition, and cell death. To evaluate the UV-B stress–induced changes in plant cells, we developed a model system based on tobacco Bright Yellow-2 (BY-2) cells. Both low-dose UV-B (low UV-B: 740 J m−2) and high-dose UV-B (high UV-B: 2960 J m−2) inhibited cell proliferation and induced cell death; these effects were more pronounced at high UV-B. Flow cytometry showed cell cycle arrest within 1 day after UV-B irradiation; neither low- nor high-UV-B–irradiated cells entered mitosis within 12 h. Cell cycle progression was gradually restored in low-UV-B–irradiated cells but not in high-UV-B–irradiated cells. UV-A irradiation, which activates cyclobutane pyrimidine dimer (CPD) photolyase, reduced inhibition of cell proliferation by low but not high UV-B and suppressed high-UV-B–induced cell death. UV-B induced CPD formation in a dose-dependent manner. The amounts of CPDs decreased gradually within 3 days in low-UV-B–irradiated cells, but remained elevated after 3 days in high-UV-B–irradiated cells. Low UV-B slightly increased the number of DNA single-strand breaks detected by the comet assay at 1 day after irradiation, and then decreased at 2 and 3 days after irradiation. High UV-B increased DNA fragmentation detected by the terminal deoxynucleotidyl transferase dUTP nick end labeling assay 1 and 3 days after irradiation. Caffeine, an inhibitor of ataxia telangiectasia mutated (ATM) and ataxia telangiectasia and Rad3-related (ATR) checkpoint kinases, reduced the rate of cell death in high-UV-B–irradiated cells. Our data suggest that low-UV-B–induced CPDs and/or DNA strand-breaks inhibit DNA replication and proliferation of BY-2 cells, whereas larger contents of high-UV-B–induced CPDs and/or DNA strand-breaks lead to cell death.